Pengaruh Kredibilitas Celebrity Endorser Terhadap Keputusan Pembelian (Studi Kasus Artis Raisa Sebagai Celebrity Endorser Produk Ice Cream Magnum Pada Mahasiswa Undip) - Abdian Fredy Wijaya; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2016)
Background of the study of this research is the development of manufacturing companies, especially tfor ice cream company. The most appropriateso that ads can be received positively by the society by choosing the celebrity endorser that had good and positive credibility. The purpose of this study is discovery to influence of credibility for celebrity endorser toward purchasing decisions for magnum ice cream product on student of Undipof the decision the purchase of products ice cream magnum on students of undip. The population in this research are students D3 and S1 are studying of Undip which are registered as an active students. The sampling techniques used multi stage sampling by determining the number of respondents as muny as 96. The result of this research showed that trustworthiness, attractiveness, and expertise became the part of credibility for celebrity endorser in giving the impact for Undip students to make a decisions for buying Magnum ice cream produtt. In regression analysis against variable attraction, they had the most dominant effect in the amount of 0.279. The suggestions that can be conveyed for this research are giving innovation flavors and design on magnum ice cream, making an attractive advertising concept, and expanding market distribution.